2021
DOI: 10.1093/jnci/djab083
|View full text |Cite
|
Sign up to set email alerts
|

Informing Women About Overdetection in Breast Cancer Screening: Two-Year Outcomes From a Randomized Trial

Abstract: Background Supporting well-informed decisions about breast cancer screening requires communicating that inconsequential disease may be detected, leading to overdiagnosis and overtreatment. Having previously shown that telling women about overdetection improved informed choice, we investigated effects on screening knowledge and participation over 2 years. Methods We conducted a community-based, parallel-group, randomised contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
4
6
0
Order By: Relevance
“…Randomised controlled trial data has shown that women can be safely informed about overdiagnosis before screening: educating women about overdiagnosis prior to screening improved understanding, reduced worry about breast cancer, and did not increase anxiety or reduce willingness to participate in breast screening. 18 This is consistent with other evidence showing that women value breast cancer screening and intend to participate in screening even when aware of the risk of overdiagnosis. 19 A systematic review on women’s values and preferences around breast cancer screening showed that women are willing to tolerate the potential harms of screening for an early diagnosis, but highlighted concern that women may not understand the concept of overdiagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Randomised controlled trial data has shown that women can be safely informed about overdiagnosis before screening: educating women about overdiagnosis prior to screening improved understanding, reduced worry about breast cancer, and did not increase anxiety or reduce willingness to participate in breast screening. 18 This is consistent with other evidence showing that women value breast cancer screening and intend to participate in screening even when aware of the risk of overdiagnosis. 19 A systematic review on women’s values and preferences around breast cancer screening showed that women are willing to tolerate the potential harms of screening for an early diagnosis, but highlighted concern that women may not understand the concept of overdiagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…However, this study shows the substantial negative impact of finding out about overdiagnosis after a diagnosis of breast cancer at least in some women. Randomised controlled trial data has shown that women can be safely informed about overdiagnosis before screening: educating women about overdiagnosis prior to screening improved understanding, reduced worry about breast cancer, and did not increase anxiety or reduce willingness to participate in breast screening 18. This is consistent with other evidence showing that women value breast cancer screening and intend to participate in screening even when aware of the risk of overdiagnosis 19.…”
Section: Discussionsupporting
confidence: 80%
“…Prior research has investigated the effect of information on benefits and harms suggesting that, against a baseline of low awareness of the benefits and harms, this information increases knowledge, and informed choice [ 28 ], whereas, another study indicated that women becoming better informed about benefits and harms of breast screening may mean they are less likely to choose to participate [ 29 ]. Additionally, consistent with the findings of our study, informing about possible risks (such as overdiagnosis) does not affect intention to participate [ 30 33 ]. Some studies have indicated that an initial acceptance of harms may decrease over later screening rounds if knowledge about the risks of participation continues to increase from the baseline of low awareness [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…Results showed significant differences between groups with significantly more women in the intervention group meeting the threshold for enhanced knowledge and informed choice regarding screening post intervention [18]. These changes remained at the 2-year follow up [19].…”
Section: Introductionmentioning
confidence: 88%